Blind recognition of MIMO-SFBC based on Symbolic eigenvalue*. Issue 3 (October 2020) - Jin, Kun; Yu, Keyuan; Yan, Wenjun
Abstract: In the blind recognition of air frequency block code signals, a blind recognition algorithm of MIMO-SFBC based on symbolic eigenvalue was proposed to solve the problems of poor recognition performance and large number of samples under the condition of low SNR. According to the symbol correlation characteristics of different air frequency block codes in frequency domain, the eigenvector sequences of different air frequency block codes are derived, symbolic eigenvalue are estimated by binary hypothesis testing, and different coding types are distinguished by decision tree classification recognition algorithm. Simulation results show that the algorithm does not need prior information such as modulation prediction, and has good recognition performance under low SNR and small sample conditions, and can be applied to engineering fields such as cognitive radio.